2020
DOI: 10.1101/2020.09.15.298042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hymenoptera associated eukaryotic virome lacks host specificity

Abstract: Recent advancements in sequencing technologies and metagenomic studies have increased the knowledge of the virosphere associated with honey bees tremendously. In this study, viral-like particle enrichment and deep sequencing was deployed to detect viral communities in managed Belgian honey bees. A substantial number of previously undescribed divergent virus genomes was detected, including a rhabdovirus and a recombinant virus possessing a divergent Lake Sinai Virus capsid and a Hepe-like polymerase. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 63 publications
(54 reference statements)
3
14
0
Order By: Relevance
“…Prompted by these results, we decided to investigate if this difference was also discernible in other studies of non-Australian viromes. We used public NGS data from Belgium ( 34 ); Israel ( 30 ); South Africa, The Netherlands, and Tonga ( 29 ); and the United States, Central America, Europe, Kenya, India, and New Zealand ( 26 ). This allowed us to compare the bee populations where V. destructor is present (most of the world) with Varroa- naive populations ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prompted by these results, we decided to investigate if this difference was also discernible in other studies of non-Australian viromes. We used public NGS data from Belgium ( 34 ); Israel ( 30 ); South Africa, The Netherlands, and Tonga ( 29 ); and the United States, Central America, Europe, Kenya, India, and New Zealand ( 26 ). This allowed us to compare the bee populations where V. destructor is present (most of the world) with Varroa- naive populations ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although they were classified as honeybee viruses, many of them infect a wide variety of insect hosts. This is particularly important under the perspective of the pollinator network, since the presence of multi-host pathogens favors interspecies virus transmission [ 413 ].…”
Section: Description Of Main Bee Pathogens and Molecular Methods For ...mentioning
confidence: 99%
“…Evidence indicating that virologists, entomologists, and ecologists are in the initial phases of characterizing the bee-associated virome is provided in a recent study that sequenced virus-augmented samples from honey bees obtained as part of a large-scale sampling effort in Belgium, coupled with in-depth analyses of existing sequence data [97]. The study by Deboutte et al not only resulted in the discovery of new virus-like sequences, virus strains, and potential recombinant viruses in honey bees, it also included bioinformatic analyses of over 5000 sequence datasets, which revealed that a high number of viral genomes were common to numerous Apidae family members, as well as widely distributed across different families within the order Hymenoptera [97].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicating that virologists, entomologists, and ecologists are in the initial phases of characterizing the bee-associated virome is provided in a recent study that sequenced virus-augmented samples from honey bees obtained as part of a large-scale sampling effort in Belgium, coupled with in-depth analyses of existing sequence data [97]. The study by Deboutte et al not only resulted in the discovery of new virus-like sequences, virus strains, and potential recombinant viruses in honey bees, it also included bioinformatic analyses of over 5000 sequence datasets, which revealed that a high number of viral genomes were common to numerous Apidae family members, as well as widely distributed across different families within the order Hymenoptera [97]. These results, coupled with smaller-scale studies documenting virus replication in species beyond that of the host(s) from which particular viruses were discovered, suggest that many Hymenopteran viruses, and likely insect viruses in general, infect a wide range of species, and thus the concepts of species-specific viruses and paradigm of "spillover" from honey bees to other bee species should be reevaluated [97].…”
Section: Introductionmentioning
confidence: 99%